2021
DOI: 10.1007/s40122-021-00242-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occipital Nerve Stimulation (ONS) on the Orbicularis Oculi Reflex Triggered by a Standardized Air Flow in Patients with Chronic Migraine—A Prospective, Randomized, Interventional Study

Abstract: Introduction: Occipital nerve stimulation (ONS) is a specific form of peripheral neuromodulation used in the treatment of chronic pain disorders. A particular field of application is in the therapy of treatment-refractory headaches, especially of chronic migraine. The precise mode of action is unknown. It is presumed that central and peripheral sensitization are reduced in patients with chronic headache. The aim of this study was to examine the effect of ONS on pain-modulatory mechanisms in the trigeminocervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They have been shown to have enhanced corneal discomfort, especially on the affected side [59] . The winking reflex induced by corneal air oscillations was increased in patients with chronic migraines [60] . Morphological changes in the corneal basal plexus, Langerhans cell aggregation, nerve regeneration and inflammation, and changes in the corneal nerve from the ocular branch of the trigeminal nerve observed in patients with migraines support the possible involvement of the peripheral system of the trigeminal nerve in migraine pathogenesis [61] .…”
Section: Corneal Pain and Trigeminal Nerve Sensitizationmentioning
confidence: 85%
“…They have been shown to have enhanced corneal discomfort, especially on the affected side [59] . The winking reflex induced by corneal air oscillations was increased in patients with chronic migraines [60] . Morphological changes in the corneal basal plexus, Langerhans cell aggregation, nerve regeneration and inflammation, and changes in the corneal nerve from the ocular branch of the trigeminal nerve observed in patients with migraines support the possible involvement of the peripheral system of the trigeminal nerve in migraine pathogenesis [61] .…”
Section: Corneal Pain and Trigeminal Nerve Sensitizationmentioning
confidence: 85%
“…Notably, in patients with CM, occipital nerve stimulation was demonstrated to markedly reduce the orbicularis oculi reflex. This finding indicates that direct counteraction of trigeminally mediated central sensitisation mitigates the effects of aversive peripheral stimulation [ 35 ]. We suggest that heightened lid tightener intensity may reduce light input triggering the trigeminal nociceptive pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Occipital nerve stimulation (ONS) devices, with implantable electrodes fixated near the occipital nerves and a pulse generator in the chest, have been studied for occipital neuralgia and refractory CM for many years. ONS may normalize the loss of condition pain modulation or directly counteract the trigeminally mediated central sensitization in these patients [42,43]. Several multi-center randomized sham-controlled trials demonstrated improvement in headache frequency, intensity, or disability [44][45][46][47]; all were published more than 5 years ago.…”
Section: Occipital Nerve Stimulationmentioning
confidence: 99%